The THU-NAOC transient survey: the performance and results from the first year. (1st February 2015) - Zhang, Tian-Meng; Wang, Xiao-Feng; Chen, Jun-Cheng; Zhang, Ju-Jia; Zhou, Li; Li, Wen-Xiong; Liu, Qing; Mo, Jun; Zhang, Kai-Cheng; Yao, Xin-Yu; Zhao, Xu-Lin; Zhou, Xu; et al.
Abstract The Tsinghua University-National Astronomical Observatories, Chinese Academy of Sciences (NAOC) Transient Survey is an automatic survey that conducts a systematic exploration of optical transients. This project utilizes a 60/90 cm Schmidt telescope at the Xinglong Station of NAOC. This survey repeatedly covers ∼ 1000 square degrees of the northern sky with a cadence of 3–4 d. With an exposure of 60 s, the survey reaches a limiting unfiltered magnitude of about 19.5 mag, which enables us to discover supernovae in their relatively young stages. We describe the overall performance of our survey during the first year and present some preliminary results.